Multilayer combline bandpass filter / Nurul Aimi Sulaiman - Sulaiman, Nurul Aimi (2011)
In this thesis, a bandpass filter using combline resonator is presented. The miniaturized band-pass filter is implemented using multilayer technique with broader bandwidth. It operates at centre frequency of 2.58GHz for satellite broadcasting application. The six pole combline resonators were designed that give 7.9 % of bandwidth with return and insertion losses in the passband are -49.833 dB and -0.7878 dB respectively. TheRO3003 substrate was used has 0.75mm thickness and a dielectric constant of 3. The circuit was simulated using Computer Simulation Technology, CST.